Pheromones: A new ergogenic aid in sport? - Papaloucas, M.; Kyriazi, K.; Kouloulias, V. (International Journal of Sports Physiology and Performance, 2015)
Nowadays, antidoping laboratories are improving detection methods to confirm the use of forbidden substances. These tests are based both on direct identification of new substances or their metabolites and on indirect evaluation of changes in gene, protein, or metabolite patterns (genomics, proteomics, or metabolomics). The World Anti-Doping Agency (WADA) officially monitors anabolic steroids, hormones, growth factors, ß-agonists, hormone and metabolic modulators, masking agents, street drugs, manipulation of blood and blood components, chemical and physical manipulation, gene doping, stimulants, narcotics, glucocorticosteroids, and ß-blockers. However, several other substances are under review by WADA. Pheromones accomplish the structure and function of life from its first step, while they have an impact on the body`s performance. Both testosterone and pheromones have an ergogenic effect that could potentially affect an athlete`s performance. The authors share their questions concerning the potential impact of pheromones in sports.